Recommendation systems with the quantum k-NN and Grover algorithms for data processing - Sawerwain, Marek; Wróblewski, Marek (Zielona Góra: Uniwersytet Zielonogórski)
In this article, we discuss the implementation of a quantum recommendation system that uses a quantum variant of the k-nearest neighbours algorithm and the Grover algorithm to search for a specific element in an unstructured database. In addition to the presentation of the recommendation system as an algorithm, the article also shows the main steps in construction of a suitable quantum circuit for realisation of a given recommendation system.
Keywords: quantum k-NN algorithm; recommendation systems; Grover algorithm; big data